A Toy Store(y) - Allen, Terry (Journal of Business Venturing, 2007)
This article was used as the starting point for a series of seven analyses that comprise a special issue on entrepreneurial narrative. This article was given to scholars with the title “A Toy Store(y)” with no other identifying characteristics. The story describes the founding and operation of a toy store in Rutland Vermont in 1965. The story describes the process of realizing an opportunity, identifying and acquiring resources to pursue this opportunity, involving and managing others, and adapting to unforeseen circumstances as new competitive conditions are encountered.